Modeling lymphocyte subset dynamics after ublituximab therapy in patients with multiple sclerosis: an Italian prospective study - Zanghì, Aurora; Di Filippo, Paola Sofia; Papale, Massimo; Rutigliano, Claudia; Moretti, Maria Claudia; Avolio, Carlo; Corso, Gaetano; D’Amico, Emanuele (Frontiers in Immunology, 2025)
Background and objectivesUblituximab, a novel, glycoengineered anti-CD20 monoclonal antibody, has recently entered clinical use for multiple sclerosis (MS). In this study, we aimed to delineate the longitudinal kinetics of circulating lymphocyte subsets over the first 6 months following ublituximab initiation. Secondarily, we aimed to investigate whether relevant baseline demographic and clinical characteristics predicted the residual counts at day 30 after infusion of CD3+CD8+ T cells and CD19+ B naive cells, the two subsets that exhibited the most distinctive early kinetics.MethodsA real-world prospective study was performed at the MS Center of Foggia, Italy. Inclusion criteria were patients with a diagnosis of relapsing MS who started ublituximab between 1 December 2024 and 31 May 2025. Longitudinal trajectories were modeled with subject-specific random-intercept linear mixed-effects models. To identify determinants of early residual depletion, linear regression models were built.ResultsA total cohort of 16 patients was enrolled, with a median age of 47 (Q1–Q3 41–58), 69% men, median EDSS of 4.5, and median body mass index (BMI) of 26.9 kg/m2. Mixed-effects models showed a significant effect of time on all lymphocyte subsets. CD3+ T cells decreased by 1,577 cells/μL immediately after ublituximab infusion (p < 0.001), returning to baseline from day 7 onward. CD3+CD8+ T cells dropped by approximately 400 cells/μL within the first week (day 7 = 44 cells/μL; 95% CI 11–77) and stabilized from day 30. CD3+CD4+ T cells fell by 1,133 cells/μL post-infusion (p < 0.001), but rebounded from day 7 and remained stable through day 180. CD19+ naive B cells remained profoundly suppressed throughout the 6 months (all p < 0.001). CD16+CD56+ NK cells showed a transient reduction of 239 cells/μL at day 0 (p = 0.004), normalizing by day 7. Regression analyses at day 30 indicate no significant baseline predictors for CD3+CD8+ T or CD19+ naive B-cell recovery (R² = 0.48 and 0.24, all p > 0.05). Infusion reactions were mild and self-limited; no adverse events occurred.DiscussionIn our cohort, ublituximab induced rapid, durable CD19+ naive B-cell depletion with only transient, reversible effects on other lymphocyte subsets and preserved immunoglobulin levels. This signature extends to older and high BMI patients, supporting ublituximab as a versatile therapeutic option across heterogeneous MS populations.